2018
DOI: 10.1186/s12879-018-2982-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the prevalence of respiratory viruses in patients with acute respiratory infections at different hospital settings in North China, 2012–2015

Abstract: BackgroundAcute respiratory infections (ARIs) are a great public health challenge globally. The prevalence of respiratory viruses in patients with ARIs attending at different hospital settings is fully undetermined.MethodsLaboratory-based surveillance for ARIs was conducted at inpatient and outpatient settings of 11 hospitals in North China. The first 2–5 patients with ARIs were recruited in each hospital weekly from 2012 through 2015. The presence of respiratory viruses was screened by PCR assays. The prevale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
39
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 46 publications
3
39
2
Order By: Relevance
“…1 Detection frequencies of respiratory viruses in Beijing and Shanghai according to matched age groups. We considered P < 0.05 to be significant (marked as an asterisk) for all analyses between two cities frequent during the summer months in Beijing and more common during autumn in Shanghai, which is consistent with previous findings [15,19,25]. Moreover, our findings that RSV and HMPV were prevalent in the spring and winter and that Flu A/B peaked in winter are consistent with those of previous studies [15,25,32,33].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…1 Detection frequencies of respiratory viruses in Beijing and Shanghai according to matched age groups. We considered P < 0.05 to be significant (marked as an asterisk) for all analyses between two cities frequent during the summer months in Beijing and more common during autumn in Shanghai, which is consistent with previous findings [15,19,25]. Moreover, our findings that RSV and HMPV were prevalent in the spring and winter and that Flu A/B peaked in winter are consistent with those of previous studies [15,25,32,33].…”
Section: Discussionsupporting
confidence: 91%
“…Our study is the first to compare respiratory viral infections and their epidemiology in hospitalized children with SARI in Beijing and Shanghai. Of the 700 patients included in the study, 78.1% tested positive for at least one virus; this rate was higher than that reported by previous studies (range, 34.6-70.3%) [18][19][20][21][22][23][24][25]. This finding may be mainly explained by some differences in the SARI case inclusion criteria, since additional criteria in our study were a normal or low leukocyte count or indrawing of the lower chest wall.…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…Influenza not only contributes to respiratory hospitalization among children aged < 18 years, it also contributes to a significant percentage of outpatient visits. One study conducted in two northern provinces of China during 2012–2015 found that influenza was the most commonly detected virus in ambulatory patients across all age groups, ( 29 ) though this study used ARI for patient screening.…”
Section: Discussionmentioning
confidence: 99%